Technical Evaluation of Elevator Performance and Capacity Planning in High-Rise Apartment Towers: A Case Study in Jakarta (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2025)
Elevator systems are critical for ensuring efficient vertical mobility, safety, and occupant comfort in high-rise residential buildings. This study presents a comprehensive performance evaluation of the elevator system in a three-tower apartment complex in Jakarta, Indonesia. The analysis integrates both qualitative and quantitative methods to assess key performance indicators, including peak load demand, round-trip time, handling capacity, recommended number of elevator units, waiting time, and estimated daily energy consumption. The peak load during the initial five-minute interval was found to range from 23 to 48 persons per tower. Elevator speeds were set at 180 m/min for Tower 1 and 150 m/min for Towers 2 and 3, resulting in round-trip time values between 183 and 208 seconds. The estimated handling capacities varied from 54 to 69 persons per elevator. To ensure optimal service performance and redundancy, four elevator units are recommended for Tower 1, and three units each for Towers 2 and 3. The projected daily energy consumption, based on a five-hour operational window, ranges from 80.51 to 96.61 kWh. The findings offer practical insights for designing energy-efficient and service-optimized elevator systems in high-density urban residential developments.